The influence of the cooling rate on the structure and corrosion properties of the multicomponent high-entropy alloy CoCrFeMnNiBe - Polonskyy, V.A.; Kushnerov, O.I.; Bashev, V.F.; Ryabtsev, S.I. (Physics and Chemistry of Solid State, 2024)
Samples of the multicomponent high-entropy alloy CoCrFeMnNiBe were obtained by the methods of casting and melt-quenching, and their phase composition and electrochemical behavior were investigated. With the help of X-ray phase analysis, it was established that the studied alloy in the as-cast state has a multiphase structure, in which there are phases with lattices of the FCC, BCC, and BeNi(Co) intermetallics (structural type B2). Quenching from the melt leads to a significant decrease in the BCC phase content. The values of stationary potentials and areas of electrochemical stability of cast and melt-quenched CoCrFeMnNiBe alloy samples, as well as corrosion current densities, were determined. It is shown that all samples of the CoCrFeMnNiBe alloy behave inertly in corrosion tests, which allows them to be considered corrosion-resistant. The results of the work can be used in the development of modern multifunctional and corrosion-resistant materials.